Analisis Permintaan Beras di Provinsi Kalimantan Tengah - Revi Sunaryati (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2016)
The purpose of this study is to analyzes the factors that influence the function of demand for rice in the province of Central Kalimantan during the last 20 years, and to determine the elasticity of demand for rice in the province of Central Kalimantan. Purposively making research sites in The Province of Central Kalimantan. Data collected in the form of secondary data that is demand for rice in the province of Central Kalimantan during the last 20 years with methods of literature arid study the documents that have been provided are obtained from agencies 1-nd private or government institutions that are related to this research The data analysis using Cobb Douglas function. The result of this study is that static analysis model adjusted R2 value of 0.945, which means the proportion of the contribution of independent variables to dependent variable amounted to 94.50%, while the remaining 5.50% is explained by other variables outside the- research such as taste, flavor and consumer Preference. Based on F test variable price of rice, the price of instant noodles, per capita income, population, and education together significantly affected the demand for rice. Based on t-test variable number of people significantly influence demand of rice at the rate of 95%, while per capita income and education variables significantly influence demand for rice at 90% confidence level. The variables specified in the model and does not affect the demand for rice in the Province of Central Kalimantan is the price of rice and the prices of instant noodles. Elasticity of demand for static model based on price elasticity, price inelastic. Based on cross elasticity, the price of instant noodles do not include substitute goods. Based on the income elasticity, per capita income, is inferior.